Landasan Teologis Tafsir Ekologis Dalam Kitab Tafsir Nusantara: (Kajian Terhadap Wacana Pemikiran Tafsir kontemporer) - Muhammad Faisal; Baihaqi Baihaqi (Prodi Ilmu Al-Qur'an dan Tafsir, 2025)
Contemporary Qur’anic exegesis examines current social phenomena, using issues like poverty, gender, and especially the environment as the basis for interpretation. This article focuses on environmental issues, highlighting growing public concern over environmental damage caused by both natural events and human actions. Such concerns have led exegetes to explore Qur’anic verses on environmental preservation, emphasizing that protecting the environment is a religious command. Three major Nusantara tafsir—Tafsir al-Azhar (HAMKA), Tafsir al-Misbah (Quraish Shihab), and Tafsir Kemenag—discuss this theme in depth. Using a descriptive qualitative method, this study finds that verses such as QS Al-Baqarah: 30, QS Al-Isra’: 27, QS Al-A’raf: 56, QS Al-Anbiya: 30, QS Ar-Rum: 41, QS Ali Imran: 190–191, and QS Ibrahim: 7 form the basis for environmental preservation in these interpretations.